Wednesday

April 23, 2014

April 23, 2014

Posted by **sky** on Wednesday, July 13, 2011 at 12:55am.

ln(3x - 2) = ln 2 - ln(x - 1)

- algebra 2 -
**Reiny**, Wednesday, July 13, 2011 at 8:33amln(3x - 2) = ln 2 - ln(x - 1)

ln(3x-2) = ln(2/(x-1))

3x-2 = 2/(x-1)

3x^2 - 5x + 2 = 2

x(3x-5) = 0

x = 0 or x = 5/3

BUT, if x=0 , ln(x-1) would be undefined,

so x = 5/3

**Related Questions**

algebra - can someone plzs help me solve the equations by finding the exact ...

Help, Math. - Solve: 3e2x + 2 = 50 a. ln 8 b. ln 0.25 c. ln 14 d. 0.5ln 16...

algebra - can you show me how to do these problems solve the equation by finding...

Pre-Calculus - I need help solving this logarithmic equation: ln x + ln (x+3) = ...

pre cal - (1/3)LN27 + 2LNx = LN(2-x) i think i just need help getting started. I...

Algebra II - Solve for X. Give exact answer in form of fraction. ln 27+ln(x-8)=...

Math differentiation - 1. y = x^x 2. y = (sin^2xtan^4x)/(x^2+1)^2 3. y = x^(1/x...

algebra - Not sure if I'm doing this right Ln(3x-4)-Ln(x+1)=Ln(2) My solution: ...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...